Los procesos de remisión tributaria no garantizan los principios de igualdad, eficiencia y suficiencia recaudatoria”. - Morocho Rivera., José Luis (2020)
The present investigation entitled: "THE TAX REFERRAL PROCESSES DO NOT GUARANTEE THE PRINCIPLES OF EQUALITY, EFFICIENCY AND SUF- FICIENCY OF COLLECTION" deals with the existing problem in the state tax sys- tem, in which, there is evidence of a violation of the principles of equality, efficiency and sufficiency of collection by the highest tax authority, during the application of referral processes with the remission of interest, fines and surcharges, The reason for this is that these processes encourage defaulting taxpayers to fail to comply with their tax obligations and also create a negative precedent with respect to those taxpayers who comply with their tax obligations on time, in addition to this, there are direct negative effects on the income that the State expects to receive from this sector, and consequently, its financial activities are not properly complied with. Through this investigation, the social and economic disadvantages, which have caused such processes to be carried out until now, are examined. The tax remission is of the nature of forgiveness, remission, amnesty of tax debts, since this is provided for in the Tax Code as a way of extinguishing the tax obligation. In recent years the re- mission processes in Ecuador have occurred repeatedly, as a result of the constant eco- nomic deficit that the State has presented, creating the need to acquire a greater amount of income from the administration, so that, in this way, future expenses or budgets can be covered. Faced with this need, the figure of remission was created, with the aim of motivating all debtors to catch up with their tax obligations, giving them as an incen- tive the remission of interest, fines and surcharges. During the last forty years there have been four major processes in Ecuador. Three of them took place in the last eleven years, which allowed an increase in the State's liquidity, favoring large companies. However, it harmed the State's financial activity by fostering a negative tax culture, creating a recurring circle, in which taxpayers or responsible parties in arrears are rewarded, while taxpayers who comply on time with their tax obligations are not recognized for their positive actions. Furthermore, in the last remittance process in 2018, the most favored were the large economic groups, since only 10% of the taxpayers contribute with more than 90% of the capital collected. Finally, this research aims to carry out a conceptual, doctrinal and legal study regar- ding the referral processes and the applicability of the principles of equality, efficiency and collection sufficiency.